Gene Expression-Genotype Analysis Implicates GSDMA, GSDMB, and LRRC3C as Contributors to Inflammatory Bowel Disease Susceptibility. - Söderman, Jan; Berglind, Linda; Almer, Sven (BioMed Research International, 2015)
To investigate the biological foundation of the inflammatory bowel disease (IBD), ulcerative colitis and Crohn's disease, susceptibility locus rs2872507, we have investigated the expression of 13 genes using ileal and colonic biopsies from patients with IBD (inflamed and noninflamed mucosa) or from individuals without IBD (noninflamed mucosa). The susceptibility allele was consistently associated with reduced expression of GSDMB (P = 4.1 × 10(-3)-7.2 × 10(-10)). The susceptibility allele was also associated with the increased expression of GSDMA (P = 1.6 × 10(-4)) and LRRC3C (P = 7.8 × 10(-6)) in colon tissue from individuals without IBD and with the reduced expression of PGAP3 (IBD; P = 2.0 × 10(-3)) and ZPBP2 (Crohn's disease; P = 7.7 × 10(-4)) in noninflamed ileum. Inflammation resulted in the reduced colonic expression of ERBB2, GRB7, MIEN1, and PGAP3 (P = 1.0 × 10(-4)-1.0 × 10(-9)) and the increased colonic expression of IKZF3 and CSF3 (P = 2.4 × 10(-7)-3.5 × 10(-8)). Based on our results and published findings on GSDMA, GSDMB, LRRC3C, and related proteins, we propose that this locus in part affects IBD susceptibility via effects on apoptosis and cell proliferation and believe this hypothesis warrants further experimental investigation.